Efficient Dynamic Floor Field Methods for Microscopic Pedestrian Crowd Simulations (Communications in Computational Physics, 2014)
Floor field methods are one of the most popular medium-scale navigationconcepts in microscopic pedestrian simulators. Recently introduced dynamic floorfield methods have significantly increased the realism of such simulations, i.e. agreement of spatio-temporal patterns of pedestrian densities in simulations with real worldobservations. These methods update floor fields continuously taking other pedestrians into account. This implies that computational times are mainly determined by thecalculation of floor fields. In this work, we propose a new computational approach forthe construction of dynamic floor fields. The approach is based on the one hand onadaptive grid concepts and on the other hand on a directed calculation of floor fields,i.e. the calculation is restricted to the domain of interest. Combining both techniquesthe computational complexity can be reduced by a factor of 10 as demonstrated by several realistic scenarios. Thus on-line simulations, a requirement of many applications,are possible for moderate realistic scenarios.